Application of the WP and SAW Methods in the Decision Support System for Recipients of Free Electricity Installation Assistance - Sitorus, Ridha Saryani; Hasugian , Abdul Halim (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The main factors causing inequality and poverty in Indonesia are education, welfare, and access to essential systems such as clean water, sterilization, and of course electricity as the main energy supplier in human daily activities. Therefore, to reduce poverty in Indonesia, the main responsibility of the government is to close the gap between groups of people by providing access to various facilities such as electricity. One of the programs initiated by the government to increase access to electricity for the poor is the free electricity installation assistance scheme. However, when providing such assistance, potential recipients must be evaluated or qualified to ensure that aid funds are distributed effectively and efficiently. And in its implementation, problems often occur related to the selection of beneficiaries which are still subjective and less objective. This can have an impact on not being on target and misappropriating aid, so that aid programs do not reach their targets. A decision support system that can help evaluate the eligibility of beneficiaries in a more objective and transparent manner is needed to resolve this issue. One strategy that can be used is the Weighted Product (WP) and Simple Additive Weighting (SAW) methods. In using a combination of the WP method, it can give weight to each criterion in determining the choice of free electricity installation assistance and the SAW method is ablei to determine the data ranking of free electricity installation assistance options. The results of this study can assist in selecting beneficiaries of free electricity installation assistance in an objective and effective way.